2020
DOI: 10.1186/s12917-019-2226-9
|View full text |Cite
|
Sign up to set email alerts
|

Full genomic characterization of a porcine rotavirus strain detected in an asymptomatic piglet in Accra, Ghana

Abstract: Background The introduction of rotavirus A vaccination across the developing world has not proved to be as efficacious as first hoped. One cause of vaccine failure may be infection by zoonotic rotaviruses that are very variable antigenically from the vaccine strain. However, there is a lack of genomic information about the circulating rotavirus A strains in farm animals in the developing world that may be a source of infection for humans. We therefore screened farms close to Accra, Ghana for animals sub-clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Initially, rotaviruses were assumed to be host specific, and it was believed that this specificity was correlated with specific genotypes. 27 The discovery of genotypes in humans that have previously been identified in animals now indicates that RVA is capable of undergoing adaptations that enable interspecies transmission. 28 The increased risk of zoonotic RV transmission in developing countries could be explained by an insufficient supply of potable water, the absence of proper medical facilities and cohabitation with farm animals.…”
Section: Rv Zoonotic Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, rotaviruses were assumed to be host specific, and it was believed that this specificity was correlated with specific genotypes. 27 The discovery of genotypes in humans that have previously been identified in animals now indicates that RVA is capable of undergoing adaptations that enable interspecies transmission. 28 The increased risk of zoonotic RV transmission in developing countries could be explained by an insufficient supply of potable water, the absence of proper medical facilities and cohabitation with farm animals.…”
Section: Rv Zoonotic Potentialmentioning
confidence: 99%
“…Initially, rotaviruses were assumed to be host specific, and it was believed that this specificity was correlated with specific genotypes 27 . The discovery of genotypes in humans that have previously been identified in animals now indicates that RVA is capable of undergoing adaptations that enable interspecies transmission 28 .…”
Section: Overview Of Rotavirus Strain Diversity In Humans and Animalsmentioning
confidence: 99%
“…Phylogenetic analysis showed that the NSP1–NSP5 genes of GDJM1 were clustered into branches of A8, N1, T1, E1 and H1, respectively ( Figure 3 ). The NSP1 segment clustered with the A8 clade, and it is likely that GDJM1 segment has a porcine origin, as porcine isolates dominate this cluster ( 23 ). The NSP1 and NSP3 segments of GDJM1 were closely related to the human strains NT0077 and UFS-NGS-MRC-DPRU4723, with nucleotide identities of 95.63% and 96.69%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although pigs and cattle may harbor group A RV infection sub-clinically at low frequency, further studies are urgently needed to better understand the dynamic of zoonotic risk involving transmission to humans 60,61 . Of note, the porcine genogroup E RVs are considered uncommon and its pathogenesis is not yet well elucidated.…”
Section: Discussionmentioning
confidence: 99%